Analisis Proses Pembelajaran Bahasa Arab Siswa kelas 1 MI Sudirman Mindi Sedayu Karanganyar Tahun Akademik Ajaran 2024/2025 - Arifah Firza Auliya (Thulabuna: Jurnal Pendidikan Bahasa Arab, 2024)
This study aims to analyse the Arabic language learning process among first-grade students at Madrasah Ibtidaiyyah Sudirman Mindi Sedayu Karanganyar in the 2024/2025 academic year. The main focus of this study is to describe the planning, implementation, and evaluation of Arabic language learning in the early grades of madrasah ibtidaiyyah, including the supporting and inhibiting factors in its implementation. This study uses a descriptive qualitative approach, with data collection techniques through observation, interviews, and documentation. The researcher uses an inductive method to draw conclusions from the collected data related to the Arabic language learning process in the first grade of Madrasah Ibtidaiyyah. The results of the study indicate that the Arabic language learning process in first grade is based on the K.13 curriculum, but it still faces challenges such as the lack of variety in teaching methods, the high number of students who cannot read the Quran, as well as the lack of knowledge and skils of teachers in teaching Arabic. Learning evaluation is conducted gradually through written assessments and direct observation. This study recommends improving teacher training and providing learning media that supports student characteristics.